Legal Protection of Consumers in Renting Video Streaming Accounts Obtained Through The Marketplace - Rizka Chellin Dwi Azizah; Chrisna Bagus Edhita Praja; Heniyatun Heniyatun; Bambang Tjatur Iswanto (Universitas Muhammadiyah Magelang, 2024)
This study aims to determine the validity of the video streaming account rental agreement through the marketplace and the protection of consumers in renting video streaming accounts through the marketplace. This research uses normative research methods with a legislative approach and literature study and is presented descriptively the results of this study explain that the agreement that occurs between the video streaming application service provider in the marketplace and the application tenant does not fulfil the validity of the agreement according to Article 1320 of the Civil Code, namely regarding the requirements of a halal cause. The tenant has violated the terms and conditions set by the official video streaming application service provider. Legal protection cannot be given to users of video streaming application services obtained through the marketplace because the objective conditions of the agreement are not fulfilled, which makes the agreement null and void and is considered never to have occurred.